Incidence of Secondary Sclerosing Cholangitis in Hospitalized Long COVID-19 Patients: A Retrospective Single Center Study - Christoph R. Werner; Stefano Fusco; Katharina Kienzle; Stefanie Döbele; Kerstin Artzner; Nisar P. Malek; Dörte Wichmann; Siri Göpel (Diagnostics, 2024)
Background: SARS-CoV-2 infection and associated COVID-19 disease can lead to critical illness with a risk of developing a multiple organ failure. Subsequently, this may lead to various pathological sequelae, such as secondary sclerosing cholangitis after surviving COVID-19 (SSC-COVID). Objective: The aim is to retrospectively analyze a cohort of hospitalized patients with first-wave (February 2020–June 2020) SARS-CoV-2 infection and persisting unclear cholangiopathy to determine the incidence of SSC-COVID and its risk factors. Results: A total of 249 patients were hospitalized at the university hospital in Tübingen, Germany, with SARS-CoV-2 infection during the first wave of the pandemic. Of these, 35.3% (88/249) required intensive care treatment; 16.5% (41/249) of them died due to the complications of COVID-19; 30.8% (64/208) of surviving patients could be followed up und were retrospectively analyzed at our center. The incidence of confirmed SSC-COVID was 7.8% (5/64). All SSC-COVID patients had an ICU stay >20 days, for invasive ventilation, positioning treatment, vasopressor treatment, but possible risk factors for SSC were not significant due to the small number of patients. Conclusions: SSC-COVID is an emerging disease in post-COVID patients with a high incidence in our single-center cohort. SSC-COVID should be considered as a differential diagnosis, if unclear cholangiopathy or cholestasis persists after SARS-CoV-2 infection.